Inhibition of NMDA Receptors Prevents the Loss of BDNF Function Induced by Amyloid β - Tanqueiro, Sara R.; Ramalho, Rita M.; Rodrigues, Tiago M.; Lopes, Luísa V.; Sebastião, Ana M.; Diógenes, Maria J. (Frontiers in Pharmacology, 2018)
Brain-derived neurotrophic factor (BDNF) plays important functions in cell survival and differentiation, neuronal outgrowth and plasticity. In Alzheimer’s disease (AD), BDNF signaling is known to be impaired, partially because amyloid β (Aβ) induces truncation of BDNF main receptor, TrkB-full length (TrkB-FL). We have previously shown that such truncation is mediated by calpains, results in the formation of an intracellular domain (ICD) fragment and causes BDNF loss of function. Since calpains are Ca2+-dependent proteases, we hypothesized that excessive intracellular Ca2+ build-up could be due to dysfunctional N-methyl-d-aspartate receptors (NMDARs) activation. To experimentally address this hypothesis, we investigated whether TrkB-FL truncation by calpains and consequent BDNF loss of function could be prevented by NMDAR blockade. We herein demonstrate that a NMDAR antagonist, memantine, prevented excessive calpain activation and TrkB-FL truncation induced by Aβ25–35. When calpains were inhibited by calpastatin, BDNF was able to increase the dendritic spine density of neurons exposed to Aβ25135. Moreover, NMDAR inhibition by memantine also prevented Aβ-driven deleterious impact of BDNF loss of function on structural (spine density) and functional outcomes (synaptic potentiation). Collectively, these findings support NMDAR/Ca2+/calpains mechanistic involvement in Aβ-triggered BDNF signaling disruption.